2022
DOI: 10.3389/fcvm.2022.984951
|View full text |Cite
|
Sign up to set email alerts
|

Are cardiovascular comorbidities always associated with a worse prognosis in patients with lung cancer?

Abstract: Many factors contribute to mortality in lung cancer, including the presence of concomitant cardiovascular disease. In the treatment of early stage of lung cancer, the presence of comorbidities and occurence of cardiotoxicity may be prognostic. The effect of cardiotoxicity of radiotherapy and chemoradiotherapy on overall survival has been documented. Acute arterial and venous thromboembolic events seem to correlate with the degree of the histological malignancy, its clinical advancement, and even with optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 131 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Echocardiography should be part of the baseline cardiovascular risk stratification before anticancer treatment. The coexistence of cardiac diseases may be associated with a worse prognosis in patients treated for cancer ( 20 ). Cancer and its treatment favor the development of new and progression of existing cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography should be part of the baseline cardiovascular risk stratification before anticancer treatment. The coexistence of cardiac diseases may be associated with a worse prognosis in patients treated for cancer ( 20 ). Cancer and its treatment favor the development of new and progression of existing cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of AF in general population varies from 1 to 2%, whereas among oncological patients, it reaches between 5% and 16%, depending on the risk factors and cancer type [ 3 , 4 ]. Korean Nationwide Population-Based Study showed that AF is strongly connected with the presence of hematological and intrathoracic cancers with HR = 2.69 for esophageal cancer and HR = 2.39 for lung cancer [ 5 •, 6 ]. In a group of 4,324,545 patients, 316,040 (7.3%) of whom had a cancer diagnosis, the incidence of AF was increased in all cancer types, in comparison to patients without cancer and reached 17.4 per 1000 person-years (PY) and 3.7 per 1000 PY, respectively, during 12 years of follow-up [ 7 ].…”
Section: Epidemiologymentioning
confidence: 99%
“… 2 , 3 Studies have shown that patients with CVD, such as heart disease, vascular disease, and hypertension, have a 67% increased risk of developing lung cancer, and patients with lung cancer and comorbid CVD, such as coronary artery disease (CAD), hypertension, arrhythmias, and peripheral atherosclerosis, have a 30% increased risk of death compared to patients with lung cancer without comorbidities. 4 , 5 Lobectomy is the most important treatment for early stage lung cancer. 6 Postoperative complications, such as prolonged hospital stay, unplanned reoperation after surgery, and readmission or death, affects patients' quality of life, reduces hospital efficiency, and reduced their social and economic benefits.…”
Section: Introductionmentioning
confidence: 99%